Primary pleural epithelioid angiosarcoma presenting with recurrent haemorrhagic pleural effusions - Eleanor Dorman; Shubhada Bansode; Rizwan Kaiser (European Journal of Case Reports in Internal Medicine, 2026)
Introduction: Primary pleural angiosarcoma is an extremely rare malignancy of the pleura arising from the vascular endothelial cells. The disease is highly aggressive and associated with a poor prognosis. Clinical and imaging features are non-specific often leading to delays in diagnosis. Case description: We report a case of primary pleural epithelioid angiosarcoma in a 66-year-old man presenting with a 2-month history of progressive dyspnoea, anorexia and significant weight-loss. Chest imaging revealed a large pleural effusion which was haemorrhagic on sampling. Multiple haemorrhagic nodules on parietal pleura were biopsied at medical thoracoscopy. Tumour morphology and immunocytochemical analysis with positive staining for endothelial markers CD31 and ERG supported the diagnosis of pleural epithelioid angiosarcoma. He was treated with palliative chemotherapy with some initial response but developed rapid disease progression after 6 months resulting in his death. Conclusion: Pleural angiosarcoma causes diagnostic uncertainty due to its rarity, non-specific presentation and inconclusive cytology. Histopathology and immunohistochemistry are crucial for prompt diagnosis of this aggressive disease.